A boundary element method formulation for modal analysis of doubly curved thick shallow shells (2016)
The study of vibrations of shells is an important aspect in the design of thin-walled structures. In general, analytical solutions for the natural frequencies of shells are not possible, and computational techniques are required. In this paper, modal analysis of shallow shells using a new boundary element method formulation is presented. The proposed formulation is based on a direct time-domain integration using the elastostatic fundamental solutions for both in-plane elasticity and shear-deformable plates. We modeled shallow shells by coupling the boundary element formulation of a shear-deformable plate and the two-dimensional plane stress elasticity. Effects of shear deformation and rotatory inertia were included in the formulation. Domain integrals related to inertial terms were treated by the dual reciprocity boundary element method. Numerical examples are presented to demonstrate the efficiency and accuracy of the proposed formulation. © 2015 Elsevier Inc.